2017
DOI: 10.1128/iai.00903-16
|View full text |Cite
|
Sign up to set email alerts
|

The Carbohydrate Lectin Receptor Dectin-1 Mediates the Immune Response to Exserohilum rostratum

Abstract: Dematiaceous molds are found ubiquitously in the environment and cause a wide spectrum of human disease, including infections associated with high rates of mortality. Despite this, the mechanism of the innate immune response has been less well studied, although it is key in the clearance of fungal pathogens. Here, we focus on Exserohilum rostratum, a dematiaceous mold that caused 753 infections during a multistate outbreak due to injection of contaminated methylprednisolone. We show that macrophages are incapa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 77 publications
2
16
0
Order By: Relevance
“…MTT assay indicated that THP-1 cells did not damage significantly the Curvularia strains. Similarly, macrophages could not inhibit conidial germination and hyphal growth of E. rostratum ( 29 ). At the same time, THP-1 cells effectively decreased the viability of A. fumigatus during their interaction, as expected based on previous studies ( 20 ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…MTT assay indicated that THP-1 cells did not damage significantly the Curvularia strains. Similarly, macrophages could not inhibit conidial germination and hyphal growth of E. rostratum ( 29 ). At the same time, THP-1 cells effectively decreased the viability of A. fumigatus during their interaction, as expected based on previous studies ( 20 ).…”
Section: Discussionmentioning
confidence: 98%
“…Although there are no available data about the response of monocytes to any similar dematiaceous mold, there are a few studies discussing the interaction of these fungi with other cell types. Recently, Reedy et al ( 29 ) found that macrophages could not phagocytose the conidia of Exserohilum rostratum , another dematiaceous mold related to Curvularia . At the same time, macrophages also showed an attraction and attachment to the hyphae of Exserohilum .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A polarizer (Nikon, MEN 51941) and Wollaston prisms (Nikon, MBH76190) were used to acquire differential interference contrast (DIC) images. Emission light from the samples was collected after passage through the appropriate emission filters (Semrock, Rochester, NY, USA) ( 32 ). Images were acquired using MetaMorph software (Molecular Devices, Downingtown, PA, USA), and processed using Adobe Photoshop CS5 and assembled in Adobe Illustrator, version CS5 (Adobe Systems, San Jose, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Not much work has been done to elucidate the mechanism of infection and immune responses against these fungi. A very recent work demonstrates the role of Dectin-1 in the recognition of Exserohilum rostratum ( 30 ). Mouse macrophages generate a Dectin-1 dependent TNF-α, IL-1ÎČ, MIP-1, and MIP-2 secretion in response to E. rostratum hyphae in vitro and the response is diminished in Dectin-1-deficient macrophages.…”
Section: Rare Disease Causing Fungimentioning
confidence: 98%